Upaya Peningkatan Pengetahuan Faktor Penyebab GTM dan Inovasi Pisang Barongko Sebagai Alternatif Bergizi dalam Pencegahan GTM di Posyandu Aster 11, Way Kandis, Bandar Lampung - Jauharoh Hanif Taqiyyah; Devita Natashya; Anisa Salwa Razika; Happy Tamara; Randi Wibowo; Laili Tsany Indhiati Prabowo; Zeta Putri Adlia; Siti Nurhaliza Hsb; Tasya Tiara Zahira; Nanda Lenny Yuniaty Br. Simorangkir; Intan Azkya Dewi; Dini Mardhiyani; Juwana Janu (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
Gerakan Tutup Mulut (GTM), or “Refusal to Eat,” is a common nutritional problem among toddlers and contributes to reduced nutrient intake and an increased risk of malnutrition. Preliminary observations at Posyandu Aster 11 Way Kandis, Bandar Lampung, indicated that mothers had low levels of knowledge regarding the causes of GTM and limited exposure to responsive feeding education. This community service activity aimed to improve mothers’ understanding of the factors contributing to GTM and to introduce pisang barongko as an innovative, nutritious snack option to help prevent GTM. The methods utilized included educational sessions through leaflets, presentations, video demonstrations, and pretest–posttest evaluation using the Wilcoxon test. The activity involved 25 participants and resulted in an improvement in knowledge scores from an average of 66 to 94.8, demonstrating a significant increase of 28.80 (p < 0.05). High participant enthusiasm, effective material delivery, and the availability of educational outputs such as videos and leaflets supported the success of the program. These findings highlight the importance of nutrition education based on local food resources as a practical and sustainable strategy to prevent GTM in children.